The Correlation Between Parents Educational Background on Student Mindset in Learning English of 10th Grade Students in SMK Ma’arif 9 Kebumen - Rohmawati, Nuzulia; Nabila, Zulfa (UM Purwokerto Press, 2025)
This research explore the correlation between parents' educational background and students' mindsets in learning English among tenth-grade students at SMK Ma'arif 9 Kebumen during the academic year 2024/2025. Utilizing Carol Dweck's theory of mindset, the study distinguishes between fixed and growth mindsets, emphasizing how these perspectives influence students' learning approaches and challenges faced in academic settings. A mixed-method approach was employed, with a sample size of 63 students selected through a random sampling technique, representing 20% of the total population. Data was collected using a Likert-type scale questionnaire designed to assess both parents' educational levels and students' mindsets, which were subsequently analyzed using Pearson's correlation coefficient. The findings revealed that the average educational background of parents fell into the low category. It can be seen from the average value of parents education level background was 29,03; it is on the interval 21 – 40. While students' mindsets were classified as having a moderate growth mindset. It can be seen from the average value of students mindset was 117,16 it is on the interval 90 – 119. However, the correlation analysis indicated no significant correlation between parents' educational background and students' mindsets in learning English. This is evidenced by the value of correlation coefficient= -0,080 , it meant very low or no significant.